ATHLETES CITIZENSHIP ISSUE IN PUBLIC INTERNATIONAL LAW - Anca-Maria IONESCU (Challenges of the Knowledge Society)
International Sports has not been spared the effects of globalization, and among these is the migration of athletes from one country to another. Lately nationality of athletes has become a major issue for professional sports and the principles on which it is based. The problem arose from the lack of a clear and consistent rules on sporting nationality for athletes representing a country in international competition. For a long time, the mere possession of nationality was sufficient to check this link to a particular state. This thesis, outlines how the rules for each sport varies quite considerably, from sports that allow a high degree of flexibility and movement for Olympics to sports that have somewhat restrictive regulations such as football or very restrictive like tennis. It also emphasizes the advantages and disadvantages of quick naturalization and provides some ideas for how this issue can be handled.